The Utility of Gallbladder Absence on Ultrasound for Children With Biliary Atresia - Ho, Andrea; Sacks, Marla A.; Sapra, Amita; Khan, Faraz A. (Frontiers in Pediatrics, 2021)
Background: Biliary Atresia (BA) is congenital condition, where infant intra- and extrahepatic bile ducts become obliterated, leading to cholestasis and cirrhosis if untreated. This study aims to assess the predictive measure of absent gallbladder on ultrasound (US) performed in infants with cholestasis for diagnosing BA. Method: After Institutional Review Board approval, retrospective chart reviews of 61 infants with cholestasis found 43 (70.5%) were diagnosed with BA. Statistical analysis was used to assess the utility of absence of gallbladder on US in predicting BA, confirmed intraoperatively. Results: Absent gallbladder on US, predicts absent gallbladder with 75% accuracy, 83% sensitivity, 73% specificity, PPV 43%, and NPV 45% (P <0.001, Fisher exact test). To diagnose BA, absent gallbladder on US has 64% accuracy, 51% sensitivity, 94% specificity, 96% PPV, and 45% NPV (P <0.001, Fisher exact test). Conclusion: Sonographic gallbladder absence has high specificity and PPV, indicating utility for BA diagnosis; however, it is not useful for BA screening given its low sensitivity.